C.S. Lewis’ Types of Love Portrayed in Sally Rooney’s Normal People - Wahyu Ningsih, Adelia Sri; Supsiadji, Mateus Rudi (Cultural Narratives, 2023)
This study aims to analyse the types of love in Sally Rooney’s Normal People. The objective of this study is to find the types of love that exist between the characters in the story. In analysing the story, the writers apply C.S. Lewis’ theory of love. The theory explains that there are four types of love, namely storge, philias, eros, and agape. The research method is descriptive qualitative research. The analysis is conducted by using intrinsic and extrinsic approaches. The intrinsic approach is applied in this study because the study deals with the characters in the novel. The extrinsic sociological approach is used to analyse love types. The data are taken from Normal People that is written by Sally Rooney. The findings show that through the characters, the novel discusses different types of love. There are only three types of love seen in the novel Normal People. The first type of storge or familial happens can be pictured through the interactions of Connell, Lorraine, and Marianne. The second type of philias or friendship is depicted in the interactions of Marianne, Connell, Joanna, and Niall. The last type of eros or romantic love happens to the character of Marianne and Connell. The conclusion, in Normal People love exists in every single person and it has some different types that happen between family, friends, and couples.